Analysis of Teachers’ Job Satisfaction in Public Primary School - Abdurrohman Abdurrohman; Yasir Arafat; Mulyadi Mulyadi (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
Teachers’ job satisfaction is the teacher's perception of what he has obtained, through the indicators compiled. In this study the indicators used are the fields of promotion, salary and incentives, promotions, coworkers as well as supervisory and leadership evaluation. The purpose of this research is to look at the level of satisfaction of teachers who teach in public  primary schools on Pulau Rimau. The method used in this research is descriptive qualitative and quantitative (mixed method). The number of objects in this study were five public  primary schools. The results obtained from the research that has been done are stated that the level of satisfaction of teachers who teach in public  primary schools in the Pulau Rimau region is included in the quite high category, but in the field of salary and incentives is an area with the highest average value of job satisfaction low.